Analisis pengembangan sektor unggulan Kota Surabaya 2013-2018 - Yusuf Hariyoko; Anggraeny Puspaningtyas (Universitas Merdeka Malang, 2020)
Law Number 23 of 2014 concerning Regional Government clause 29 verse 5 explains that